Effect of an educational intervention on the knowledge level of toxoplasmosis in pregnant women attending a health center in Lurin, 2023 - Hiyo B., Melissa Cristell (2025)
The objetive of the study was to determine the effect of an educational intervention on the knowledge level of toxoplasmosis among women in the first two-thirds of pregnancy attending the maternal-child health center in Lurín, Lima, Peru, during July-August 2023. An assessment tool comprising 20 multiple-choice questions was developed and administered before, immediately after, and four months post a virtual educational intervention involving 31 women in their first or second trimester of pregnancy. The educational intervention consisted of three sessions delivered synchronously via a virtual platform. Knowledge levels were classified using a scoring scale ranging from 0 to 20 points, based on criteria established by the Ministry of Education. Results showed that prior to the educational intervention, 64.5% (20/31) ± 0.168 of the pregnant women had a knowledge level classified as "poor". However, following the intervention, 74.2% (23/31) ± 0.154 of participants achieved a knowledge level considered "good". In the long-term evaluation, 38.7% (12/31) ± 0.171 of the sample attained a knowledge level classified as "good", while an equal percentage (38.7%) obtained a "regular" classification. In conclusion, the educational intervention had a positive effect on the knowledge level regarding toxoplasmosis among pregnant women in the first or second trimester in both short-term and long-term assessments (p < 0.05).